Employee satisfaction with offshore catering job: piloting for interviews - Abdul Majid, Mohd Aliff; Othman, Mohhidin; Mohamad, Siti Fatimah; Abdul Halim Lim, Sarina (Human Resource Management Academic Research Society, 2017)
Previous studies indicate that employee’s job satisfaction plays a major role in organizational performance. This study draws upon qualitative investigation with offshore catering employees; the main aim was to explore their satisfaction with the job. Although there have been a numerous number of studies, the area remains to experience range of grasps and ambiguity in this discourse. Shifting the focus from usual job setting where job satisfaction is commonly studied, researchers draw on the findings to gain insights into these differing understandings of offshore catering employees as they engaged in secluded and confined workplace. The pilot interview was carried out as impetus for a dissertation in constructing a bespoke job satisfaction instrument. In this small-scale pilot study, this study explored the job satisfaction experiences of Mark and Karl, two offshore catering employees. Data in the form of in-depth, semi-structured interviews identified 44 codes, indicating 10 dimensions of job satisfaction derived from the emerging themes. Evidently, the qualitative findings present meaningful attributes of job satisfaction among offshore catering employees. Apparently, findings of this study shed light on the need for future research to extend the scope of the study, bringing diverse cultures in order to improve the understanding of job satisfaction across a broader spectrum.